PERBANKAN ISLAM VS PERBANKAN KONVENSIONAL PADA MASA PENGUMUMAN BREXIT - yoesoef, yoesrizal muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2019)
Abstrac On 22nd February 2016, the Prime Minister of the United Kingdom, David Cameron, announced there would be a referendum on whether the UK should remain within the European Union or not. The referendum took place on Thursday 23rd June. Confirmation of the result came on Friday 24th June and was in favour of Brexit. The aim of this research is to review the stability between Islamic banking and conventional banking in the face of global crisis period during the Brexit is announced. This research is based on financial data from three conventional banks and three Islamic banks as representatives that will be measured using the event study method, which is the observation of stock prices during the observation period. Analysis emphasizes the importance of the institutional and economic environment, as well as the targeted profitability of the Bank and the method by which international Banks acquire share ownership, as a significant determinant of Abnormal returns. By measuring stock movements during the Brexit announcement period, we can find out whether the crisis during Brexit affects Islamic banking stability or vice versa. For this reason, the writer also applied the research hypothesis which was carried out with a Student t-test that could help to see the current condition of the Bank's performance compared to past performance.   Keywords: Islamic Banking, Conventional Banking, Brexit   Abstrak Tujuan dari studi ini adalah meninjau kestabilan antara perbankan Islam dan perbankan konvensioanal dalam menghadapi masa krisis global yaitu pada masa Brexit diumumkan. Penelitian ini berdasarkan data keuangan dari tiga Bank konvensional dan tiga Bank Islam sebagai representatif yang akan diukur dengan menggunakan metode studi even study (Identifikasi Peristiwa) yaitu pengamatan harga saham pada periode pengamatan. Analisa menegaskan pentingnya lingkungan kelembagaan dan ekonomi, serta profitabilitas Bank yang ditargetkan dan metode di mana Bank-Bank internasional memperoleh kepemilikan saham, sebagai penentu signifikan dari return tidak normal (Abnormal return)[1]. Dengan mengukur pergerakan saham pada masa pengumuman Brexit, kita dapat mengetahui apakah krisis pada masa Brexit diumumkan ini mempengaruhi kestabilan perbankan Islam ataupun sebaliknya. Untuk itu, peneliti juga menerapkan hipotesis penelitian yang dilakukan dengan Student t-test yang dapat membantu melihat kondisi kinerja Bank saat ini dibandingkan kinerja masa lalu.   Kata Kunci: Perbankan Islam, Perbankan Konvenional, Brexit   *Penulis adalah dosen Perbankan Syariah IAIN Lhokseumawe, Aceh, Email: yoesrizal@iainlhokseumawe.ac.id [1] Abnormal return adalah selisih antara tingkat keuntungan yang sebenarnya dengan tingkat keuntungan yang diharapkan.